Antifungi Effect of Keghenyat Leaves Fraction (Acmella uliginosa) In Vitro Study - Agustina Septi Hijir; Salni Salni; Joko Marwoto; Triwani Triwani; Sri Nita; Mgs Irsan Saleh; Ziske Maritska; Nita Parisa; Evi Lusiana; Nia Savitri Tamzil; Ayeshah Augusta Rosdah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2017)
Introduction Candida is a yeast fungus classes most commonly found in the oral cavity, gastrointestinal tract, reproductive tract and skin, especially the species Candida albicans. Alternative medicines such as herbs are easily available and affordable by the community, such as keghenyat leaves (Acmella uliginosa). Aim of StudyTo determine the activity of Keghenyat leaves fraction (Acmella uliginosa) compared to Nystatin against Candida albicans in vitro. MethodsIn vitro study was held in Laboratory of Genetics and Biotechnology Department of Biology, Faculty of Science and Medical Faculty, Sriwijaya University in December 2015 and January 2016. Research stages: extraction, fractionation, sensitivity test using Nystatin and Candida albicans, fractions antifungal activity test, the determination of minimum inhibitory concentration (MIC), bioautografi test and determination of compound classes. One final stages of testing the active fraction Keghenyat leaves (Acmella uliginosa) with Nystatin. Data were analyzed using ANOVA and Post Hoc Duncan test and linear regression using SPSS 20. ResultsHexane faction of Keghenyat leaves (Acmella uliginosa) is active against the fungus Candida albicans, has a Minimum Inhibitory Concentration (MIC) of 0.625% (6250Î¼l) against the fungus Candida albicans antifungal contain active compounds that terpenoids and flavonoids, amounting to 84.68 mg / ml equivalent to 1 mg / ml Nystatin against the fungus Candida albicans. ConclusionThere is a significance different MIC between hexane fraction of Keghenyat leaves (Acmella uliginosa) and Nystatin, Nystatin have more high activity.